2007
DOI: 10.1080/02713680601090965
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Concentrations of Kynurenic Acid, a Tryptophan Derivative, in Dense Nuclear Cataracts

Abstract: KYNA levels are elevated in senile nuclear human cataracts and in cataractous lenses of rats with experimentally induced diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…2001, 2003) and in human, bovine and rabbit vitreous body (Żarnowski 2004). Recent study has shown presence of KYNA in human cataractous lens (Żarnowski et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2001, 2003) and in human, bovine and rabbit vitreous body (Żarnowski 2004). Recent study has shown presence of KYNA in human cataractous lens (Żarnowski et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of KYNA has been documented in urine, serum, amniotic fluid (Milart & Sikorski 1998), cerebrospinal fluid (Swartz et al 1990), retina in rats, chickens, DBA ⁄ 2J mice (Rejdak et al 2001(Rejdak et al , 2003 and in human, bovine and rabbit vitreous body ( _ Zarnowski 2004). Recent study has shown presence of KYNA in human cataractous lens ( _ Zarnowski et al 2007). However, little is known about the role of KAT in cataract formation.…”
mentioning
confidence: 99%
“…A tryptophan-free diet induces cataracts in young Wistar rats, along with a significant decrease in lens weight and water-soluble lens protein [185]. Kynurenine is a breakdown product of tryptophan, and it has been suggested that kynurenine and its glycoside derivatives in the ocular lens protect the retina from UV light by absorbing UV radiation [186]. Kynurenine is present in excessive concentrations in cataracts [186].…”
Section: Cataracts and Melanomamentioning
confidence: 99%
“…Kynurenine is a breakdown product of tryptophan, and it has been suggested that kynurenine and its glycoside derivatives in the ocular lens protect the retina from UV light by absorbing UV radiation [186]. Kynurenine is present in excessive concentrations in cataracts [186].…”
Section: Cataracts and Melanomamentioning
confidence: 99%
“…In recent years, many researches have proven a significant role of the KP in the pathogenesis of several serious disorders, such as cancer, psychiatric, neurodegenerative and autoimmune system dysfunctions [ 3 ]. The examination of TRP metabolites levels has been studied in brain tissue and amniotic fluid [ 4 ], serum [ 5 , 6 ] cerebrospinal fluid [ 7 ], human cataracts’ lenses [ 8 ] and saliva of a diabetic patient [ 9 ]. There is also evidence that the KP pathway is connected with visual function as KYN and 3-OH-KYN glycoside derivatives act as UV filters and protect the retina and the lens by absorbing the UV radiation [ 8 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%